New Model Policy Implementation Gerbang Emas Bersinar to Increase the Human Development Index in Tabalong Regency - Anang Syakhfiani; Sampara Lukman; Khasan Effendy; Marja Sinurat (International Journal of Science and Society, 2020)
Tabalong Regency Human Development Index shows positive growth from year to year from 68, 08 in 2013 to 70.76 in 2017. The Implementation of the development movement policy towards prosperous communities or “Gerbang Emas Sejahtera” has been proven successful in increasing the HDI of Tabalong Regency. However, this policy is still felt to be less than optimal in terms of the welfare of the community because here the nature of the policy is still top-down where the government's role is still very dominant in terms of being a facilitator and policy initiator. Policies are needed that can provide a productive reciprocal relationship between government and society. This research tries to introduce a new model of policy implementation, namely mixed mode as a solution to the problem.